2019
DOI: 10.1155/2019/2941861
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Serum Asymmetric Dimethylarginine Level and Microvascular Complications in Diabetes Mellitus: A Meta-Analysis

Abstract: Objective. The purpose of the meta-analysis was to evaluate the relationship between serum asymmetric dimethylarginine (ADMA) level and microvascular complications in diabetes mellitus (DM) including diabetic retinopathy (DR), diabetic neuropathy (DN), and diabetic nephropathy. Methods. Studies were comprehensively identified by searching Web of Science, Embase, and PubMed databases up to August 30, 2018. The meta-analysis was carried out to compare the difference of serum ADMA concentrations of DR, DN, and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Another systematic review also showed that citrulline might be a potential biomarker of DR(Hou XW, 2021 Aug 2;62(10):4). Mechanism researched suggested that citrulline level is related to asymmetric dimethylarginine (ADMA), which is associated with DR (Liu et al, 2019). A recent meta-analysis determined that elevated serum levels of ADMA are associated with microvascular complications of diabetes including diabetic retinopathy, which con rms the views above (Liu et al, 2019).…”
Section: Discussionmentioning
confidence: 91%
“…Another systematic review also showed that citrulline might be a potential biomarker of DR(Hou XW, 2021 Aug 2;62(10):4). Mechanism researched suggested that citrulline level is related to asymmetric dimethylarginine (ADMA), which is associated with DR (Liu et al, 2019). A recent meta-analysis determined that elevated serum levels of ADMA are associated with microvascular complications of diabetes including diabetic retinopathy, which con rms the views above (Liu et al, 2019).…”
Section: Discussionmentioning
confidence: 91%
“…Elevated ADMA and SDMA levels are tied up with an increased cardiovascular risk and mortality 28 and can be found in several renal, pulmonary, cancer, and neurological conditions 29 . In diabetic neuropathy, the link with increased ADMA levels is more likely to be based on microvascular complications 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown that elevated ADMA concentrations are found in subjects with type 1 DM [ 25 , 26 ], type 2 DM [ 12 ] and poor glycemic control [ 27 ]. Furthermore, the circulating level of ADMA is relevant to several DM-related complications, such as microvascular complications [ 28 , 29 ], cardiovascular complications [ 30 ], and diabetic nephropathy [ 31 ]. Given that subjects who have the AA genotype show higher ADMA concentrations [ 32 ], the elevated CBS in the AA genotype of AGXT2 is caused by changes in ADMA levels.…”
Section: Discussionmentioning
confidence: 99%